2021
DOI: 10.1093/cid/ciab577
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of the Impact of Sociodemographic Inequalities on Adverse Outcomes and Excess Mortality During the Coronavirus Disease 2019 (COVID-19) Pandemic in Mexico City

Abstract: Background The impact of the COVID-19 pandemic in Mexico City has been sharp, as several social inequalities at all levels coexist. Here, we conducted an in-depth evaluation of the impact of individual and municipal-level social inequalities on the COVID-19 pandemic in Mexico City. Methods We analyzed suspected SARS-CoV-2 cases, from the Mexico City Epidemiological Surveillance System from February 24th, 2020, to March 31 st,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…At the individual level, we confirmed that certain socially vulnerable occupations experienced unequal risks for non-COVID-19 mortality. The role of individual and sociodemographic determinants in the risk for adverse COVID-19 outcomes has been previously explored (36,37). Nevertheless, our findings demonstrate that sociodemographic inequalities impacted individuals with preventable chronic conditions, regardless of public healthcare policies aimed at mitigating the impact of the COVID-19 pandemic in healthcare infrastructure and provision.…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, we confirmed that certain socially vulnerable occupations experienced unequal risks for non-COVID-19 mortality. The role of individual and sociodemographic determinants in the risk for adverse COVID-19 outcomes has been previously explored (36,37). Nevertheless, our findings demonstrate that sociodemographic inequalities impacted individuals with preventable chronic conditions, regardless of public healthcare policies aimed at mitigating the impact of the COVID-19 pandemic in healthcare infrastructure and provision.…”
Section: Discussionmentioning
confidence: 99%
“…Based in the “Social Determinants of Health” approach and the ecosocial epidemiology, the cumulative and dynamic interplay processes of exposure, susceptibility, and resistance, which influences health at the singular and general levels, could have been an important factor to understand processes which shape population health—as well as the COVID-19 pandemic [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between COVID-19 and some social determinants in Mexico has been studied [ 7 , 29 32 ], however, some important questions remain with this topic. Thus, the present study explores the association of living in municipalities with higher rates of crowding conditions and poverty and the risk of mortality from COVID-19 in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Although an important increase in testing capacity occurred with the introduction of antigen tests in Mexico City after 28 October 2020 [ 18 ], this pattern of testing rates by age category did not change, which suggests that low availability of testing may not determine whether younger people and older adults seek testing or not. Rather, lower testing rates in older adults, children and adolescents could be explained by the tendency to stay at home during the pandemic [ 19 ], as well as lower contacts with other people, and lower mobility indexes than young adults and middle-aged adults [ 20 ].…”
Section: Discussionmentioning
confidence: 99%